Development of MMC-based lithium molybdate cryogenic calorimeters for AMoRE-II - Agrawal, Aman; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana; Kempf, Sebastian (The European physical journal. C, Particles and fields, 2025)
The AMoRE collaboration searches for neutrinoless double beta decay of $$^{100}$$Mo using molybdate scintillating crystals via low temperature thermal calorimetric detection. The early phases of the experiment, AMoRE-pilot and AMoRE-I, have demonstrated competitive discovery potential. Presently, the AMoRE-II experiment, featuring a large detector array with about 90 kg of $$^{100}$$Mo isotope, is under construction. This paper discusses the baseline design and characterization of the lithium molybdate cryogenic calorimeters to be used in the AMoRE-II detector modules. The results from prototype setups that incorporate new housing structures and two different crystal masses (316 g and 517-521 g), operated at 10 mK temperature, show energy resolutions (FWHM) of 7.55-8.82 keV at the 2.615 MeV $$^{208}$$Tl $$γ $$line and effective light detection of 0.79-0.96 keV/MeV. The simultaneous heat and light detection enables clear separation of alpha particles with a discrimination power of 12.37-19.50 at the energy region around $$^{6}$$Li$$(n,α )^3